Operation Strategy for Contractors What is beyond lean? - ABAJI, IBRAHIM; ALHASHHOUSH, HASAN (My University, 2019)
All construction companies have an operation strategy that leads them to achieve their overall strategy or business strategy. However, an operation strategy is not always explicitly depicted within construction companies which results in poor implementation at the operational level. Operation strategies for construction companies constitutes important processes and functions that affect the progress of the construction company in both short and long term. Lean construction has been known for more than two decades as an operation strategy that could help the contractors to save time and cost as much as possible. However, the application of lean construction into the operation strategy of the contractors is considered low compared to the application of the traditional operation strategy. In this study, a literature review has been done in order to understand the current theoretical advancement regarding both the contractor operation strategy and lean construction. Four case studies of different contracting companies in Sweden have been studied also in order to investigate the current application of lean construction in the market and how to adjust lean construction implementation according every contractor's needs. There are three ways discussed of implementing lean construction in this research, implementing lean fully, partially or trying to investigate a way to achieve lean construction goals without the need of implementing lean tools. The researchers have found that the application of lean construction in Swedish market is mainly partial and the understanding of lean construction in the market is not as an operation strategy, instead, it is just a group of tools that help the contractors to achieve more with less time and waste.
Keywords: operation strategy; lean construction; construction; contractor; building; just-in-time; production